2006
DOI: 10.1097/01.mlr.0000204106.64619.2a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Changing the Statistical Methodology on Hospital and Surgeon Ranking

Abstract: Shrinkage estimators based on random-effects models are slightly more conservative in identifying quality outliers compared with the traditional approach based on fixed-effects modeling and standard regression. Explicitly modeling surgeon provider effect (fixed-effects and random-effects models) did not significantly alter the distribution of quality outliers when compared with standard logistic regression (which does not model provider effect). Compared with the standard parametric approach, the use of a boot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 36 publications
1
66
1
Order By: Relevance
“…Recently, it was found that hospital rankings may change considerably on the COPD AND SMOKING-RELATED DISORDERS N. AGABITI ET AL. basis of the risk-adjustment models used and that the classification of ''outlier status'' depends on the chosen threshold for statistical significance [22,23]. In our study, a less conservative approach, using p,0.1, could have implied more high and low outliers.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, it was found that hospital rankings may change considerably on the COPD AND SMOKING-RELATED DISORDERS N. AGABITI ET AL. basis of the risk-adjustment models used and that the classification of ''outlier status'' depends on the chosen threshold for statistical significance [22,23]. In our study, a less conservative approach, using p,0.1, could have implied more high and low outliers.…”
Section: Discussionmentioning
confidence: 88%
“…15 A fixed-effects models results in an unbiased estimate of the hospital effect when correlated with observable patient risk factors. The model was evaluated for discrimination using the c-statistic.…”
Section: Main Outcome Measure and Statistical Analysismentioning
confidence: 99%
“…Multiplying the O:E ratio by the outcome's mean yields the risk-adjusted rates. 15 All statistical analyses were conducted using STATA special edition (version 13, StataCorp, College Station, TX).…”
Section: Main Outcome Measure and Statistical Analysismentioning
confidence: 99%
“…From this we derived relative risks (RRs) for each hospital using predicted probabilities from only the fixed effects part of the model. 27,28 We used the noblup ilink options within PROC GLIMMIX to achieve this. These RRs are akin to standardised mortality ratios (SMRs), which represent the ratio of the hospital's rate to the national average rate.…”
Section: Modelling Frameworkmentioning
confidence: 99%